Political Mobilisation, Ethnic Diversity and Social Cohesion: The Conditional Effect of Political Parties. (20th November 2013) - Helbling, Marc; Reeskens, Tim; Stolle, Dietlind
<x xml:space="preserve">Abstract</x> Recent research on the consequences of ethnic diversity for social cohesion indicates that the effects of diversity are not necessarily universal. In this article we hypothesise that the rhetoric of political parties conditions whether diversity negatively affects generalised trust. Political campaigns might highlight the salience of cultural diversity issues in their discourse or, moreover, use a divisive rhetoric of 'nationalistic' positions. Thus political mobilisation might heighten the perceived conflict between those who are native born and immigrants, especially in diverse societies. In order to test this argument, we investigate the influence of political rhetoric framed on cultural diversity issues, that is, nationalism and multiculturalism – obtained from the Comparative Manifestos Project– on generalised trust in 21 European democracies. We find that the negative impact of ethnic diversity on trust is particularly strong when these issues are mobilised by political parties. It does not, however, matter whether these issues are presented in a positive or negative light.